What influences aromatase inhibitor continuation intention among breast cancer survivors? - Young Kyung Seo; Jeongok Park; Jin-Hee Park; Sue Kim (Korean Journal of Women Health Nursing, 2021)
Purpose Aromatase inhibitors (AIs) are widely prescribed for postmenopausal women with breast cancer and are known to cause musculoskeletal pain. This study aimed to identify factors associated with AI continuation intention among breast cancer survivors (BCS). Methods A cross-sectional survey was conducted on 123 BCS (stages I–III), who had been taking AIs for at least 6 weeks. Participants were recruited from a cancer center in Goyang, Korea, from September to November 2019. Descriptive statistics, Welch analysis of variance, Pearson correlation coefficients, and simple linear regression were used for the analysis. Results Beliefs about endocrine therapy was a significant predictor of AI continuation intention (β=.66, p<.001). The majority of participants (87.0%) reported experiencing musculoskeletal pain since taking AIs and the score for the worst pain severity within 24 hours was 5.08±2.80 out of 10. Musculoskeletal pain, however, was not associated with AI continuation intention. Fear of cancer recurrence (FCR) was clinically significant (≥13) for 74.0% of the respondents (mean, 17.62±7.14). Musculoskeletal pain severity and pain interference were significantly associated with FCR (r=.21, p<.05; r=.35, p<.01, respectively). Pain interference was significantly associated with beliefs about endocrine therapy (r=–.18, p<.05). Conclusion AI continuation intention can be modified by reinforcing patients’ beliefs about endocrine therapy. Musculoskeletal pain may have a negative effect on beliefs about endocrine therapy and increase FCR among BCS. Thus, awareness of musculoskeletal pain during AI therapy should be raised and further research is required to develop multidisciplinary pain management strategies and clinical guidelines to reinforce beliefs about endocrine therapy.